Pemanfaatan Google Form Untuk Menunjang Kinerja Proses Pendataan Dan Informasi Pada Kelurahan Pabuwaran - Ina Maryani; Sopian Aji; Safitri Linawati; Dini Silvi Purnia (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The rapid development of the use of the internet in Indonesia has made technology develop in all fields in society. During the Covid-19 pandemic, internet use is very important in all activities in the community, one of which is activities in Pabuwaran Village as one of the community activity institutions, Pabuwaran Village is expected to be able to transform their activities towards digitalization. However, the lack of knowledge of some of the existing staff has made the use of technology not implemented optimally. Lack of information, knowledge and insight into digitalization makes them unable to optimally transform to a digital system. Google Form is part of the search engine or google on the Internet that is most often used. Methods of Implementation This community service is carried out offline while still meeting the provisions and procedures that have been set by the relevant officials. By holding this activity, it is hoped that it can provide increased knowledge and skills for participants, open insight and knowledge in the use of technology, and open a community digital mindsite